Kohärenz und Resilienz in Familien mit geistig und körperlich behinderten Kindern - Retzlaff, Rüdiger; Hornig, Stefanie; Müller, Birgit; Reuner, Gitta; Pietz, Joachim (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2006)
Drawing from concepts from family stress theory, resilience theory, Holland's model of family adaptation to disability, and Antonovsky's salutogenetic model, this study explores the relationship between family sense of coherence and measures of family functioning, levels of stress, severity of the handicaps levels of functional impairment and demographic indicators. Participants were 37 families with children under 18 years with mental retardation and physical-neurological disorders that consulted the Department of Pediatric Neurology. With a discriminant analysis, measures contributing to the separation into subgroups of families with high, medium and low family cohesion were identified. The measures permitted a satisfactory discrimination into groups in this clinical sample. The highest discriminatory power held sociodemographic variables, severity of impairment, as well as levels of family functioning and measures of family coping, which are potentially amenable to therapeutic change. The results indicate that family coherence can be regarded as a global resource contributing to family resilience, and therapeutic implications are being discussed. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Gesehen am 21.02.2019